WNT signaling patterns in fish tissue - Μαραβέλια, Αγγελική (2022)
The Wnt signaling pathway is a complicated protein network which plays a crucial role in both human and animal organisms. It is proven that this network participates in cell polarity, proliferation and migration, neural patterning and organogenesis during embryonic development. Wnt proteins can activate several different intracellular signaling pathways. This study focuses in the canonical pathway Wnt/b-catenin and the non-canonical which further divided Wnt/PCP signaling pathway and Wnt/Ca2+ both compete the canonical pathway. Through research in online resources, data from the expression of different genes in Zebrafish were recorded in order to study Wnt signaling patterns. Next step was the preparation of tissue samples following the Immunohistochemistry protocol. The tissues were prepared through fixation, embedding, sectioning and most important staining and analyzed in a confocal microscope for monitoring the expression of the four different proteins (Wnt5a, Wnt11, Dvl1, Dvl3) that are used in four different wild type fishes (Chelidonichthys cuculus, Scomber scombrus, Microstomus kitt, Pleuronectes platessa). Each one of the proteins is a ligand on a canonical or a non-canonical pathway, primary antibodies and secondary fluorescence labeled antibody will be placed in fixed samples in order to bind to specific antigens in the surface of the tissue